MANAGEMENT OF SUSTAINABLE SEAWEED (Kappaphycus alvarezii) AQUACULTURE IN THE CONTEXT OF CLIMATE CHANGE MITIGATION - Erlania Erlania; I Nyoman Radiarta (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2014)
Seaweed is an important aquaculture commodity that could contribute on climate change mitigation, related to its ability on absorbing CO2, as one of the green house gases, through photosynthesis. This study aimed to analyze seaweed potencies on carbon sequestration in the context of climate change mitigation while still resulting optimum production as primary purpose and to analyze the carrying capacity of Gerupuk Bay in order to manage sustainability of seaweed aquaculture. Seaweed, (Kappaphycus alvarezii) was cultivated with long-line system in Gerupuk Bay, West Nusa Tenggara, during five months for three cultivation cycles. Samplings were conducted at days-15, 30, and 45 with CO2 absorption rates as main parameters. Water carrying capacity was calculated to determine the ability of Gerupuk Bay waters for supporting development of sustainable seaweed aquaculture. The results showed that absorption rates of CO2 by seaweed (K. alvarezii) were different at each sampling days of cultivation periods; the highest value was at 10-20 days of cultivation. CO2 absorption analysis resulted based on sampling days of cultivation period could be appl ied to formulate the strategies for management of sustainable seaweed aquaculture, with optimal production and positively contributed to the environment. However, waters carrying capacity should also be considered as major aspect in the application of seaweed cultivation management, thus it can run continuously without causing conflicts with other interests.